Laparoscopic gastric bypass to robotic gastric bypass: time and cost commitment involved in training and transitioning an academic surgical practice. Issue 2 (June 2016) - Lyn-Sue, Jerome; Winder, Josh; Kotch, Shannon; Colello, Jacob; Docimo, Salvatore
Abstract The Roux-en-Y gastric bypass is the gold standard procedure for weight loss. This relatively complex procedure has excellent outcomes when performed via laparoscopy. The advent of the DaVinci robotic platform has been a technological advancement. Our goal is to provide information regarding the cost, time commitment, and advantages of transitioning an LRYGB program to an RRYGB program in an academic setting. We retrospectively reviewed the last 25 laparoscopic gastric bypass procedures and the first 25 robotic gastric bypass procedures performed by a single surgeon. We compared clinical outcomes and focused on time and hospital cost during this transition phase. There was no significant demographic difference between the groups. The mean age was 41.7 (RRYGB) years vs 43.4 (LRYGM) years. The mean BMI were similar between groups, 45.3 vs 46.5 kg/m2 for RRYGB and LRYGB. No anastomotic leaks or mortalities were noted. There was one anastomotic stricture in both groups. Excess weight loss was similar in both groups at 1 year. There was a significant increase in operative time with RRYGB, mean 241 min vs mean 174 min (p = 0.0005). Operative time fell by 25 min after the first 10 cases. The hospital cost was also increased with RRYGB mean 5922 vs 4395 (p = 0.03). Transitioning from a laparoscopic to a robotic practice can be done safely, however, the initial operative times were longer and the hospital cost was higher for robotic gastric bypass. We hope in the future that these will decrease after overcoming the learning and as the technology becomes widespread.